PENGEMBANGAN MEDIA PEMBELAJARAN PAI BERBASIS VIDEO ANIMASI INTERAKTIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Muhammad Rifki Hidayat; Trisnawati Trisnawati; Abdul Hamid (YHMM PUBLISHING, 2025)
The development of digital technology encourages the innovation of Islamic Religious Education (PAI) learning media in elementary schools to be more interactive and interesting. However, PAI learning is still dominated by conventional methods that cause low motivation and student learning outcomes. This research aims to develop interactive animation video-based learning media to improve the motivation and learning outcomes of grade V students of Cambang 3 State Elementary School. The research method uses a Research and Development (R&D) approach with the stages of needs analysis, design, application development, trial, and evaluation. The trial was conducted on 23 students using a simple questionnaire and evaluation of PAI learning outcomes. The results showed that the level of student interest in the application reached 86.95%, while the results of the learning evaluation increased from an average of 68.26 to 84.13 or an increase of 23.24%. Interactive animated video media has been proven to be able to increase student involvement, motivation, and understanding so that it is suitable for use as a PAI learning medium in elementary schools.